Target-Based Virtual Screening of Natural Compounds Identifies a Potent Antimalarial With Selective Falcipain-2 Inhibitory Activity - Uddin, Amad; Gupta, Sonal; Mohammad, Taj; Shahi, Diksha; Hussain, Afzal; Alajmi, Mohamed F.; El-Seedi, Hesham R.; Hassan, Imtaiyaz; Singh, Shailja; Abid, Mohammad (Frontiers in Pharmacology, 2022)
We employed a comprehensive approach of target-based virtual high-throughput screening to find potential hits from the ZINC database of natural compounds against cysteine proteases falcipain (FP-2 and FP-3). Molecular docking studies provided the initial hits showing high binding affinity and specificity towards FP2 were selected. Further, the enzyme inhibition and Surface Plasmon Resonance assays were performed which resulted in a compound ZINC12900664 (ST72) with potent inhibitory effect on purified FP2. ST72 exhibited strong growth inhibition of Chloroquine sensitive (CQS) (3D7; EC50=2.8 µM) and Chloroquine resistant (CQR) (RKL-9; EC50=6.7 µM) strains of Plasmodium falciparum. Stage specific inhibition assays revealed a delayed and growth defects during parasite growth and development in parasite treated with ST72. Further, ST72 significantly reduced parasite load and increased host survival in a murine model infected with Plasmodium berghei ANKA. No Evans blue staining in ST72 treatment indicated that ST72 mediated protection of blood-brain barrier integrity in mice infected with P. berghei. ST72 did not show any significant hemolysis or cytotoxicity against human HepG2 cells suggesting a good safety profile. Importantly, ST72 with CQ resulted in improved growth inhibitory activity than individual drugs both in vitro and in vivo studies.